Effects of ten days programmed training treatment of the measured specific-motor abilities of basketball players 15 years of age - Rubin, P. (Serbian Journal of Sports Sciences, 2009)
The research took place in the basketball camp "Kikinda 07". The sample consisted of 20 basketball players, 15 years of age (± 6 months), from Kikinda's basketball clubs. For initial (9th August) and final (19th August 2007) measurements, 8 tests to measure specific motor abilities (SMA) were applied. The aim was to prove 10-day training's effectiveness (15 trainings at 90 min.) on specific motor abilities of cadets. Basketball cadets were trained under the program designed by the author of this research. The differences between the two measurements were proven using multivariate analysis of variance. The statistically significant difference appeared between two measurements at the levels of 0.00. In the final measurement, univariate analysis of variance showed significantly better results after training in 4 tests (variable): "Kamikaze" shortened with driving (at the level of 0.05); Driving the ball around the central circle (at the level of 0.00) for measuring SMA movement of the player with the ball; and for SMA ball manipulation: Dribbling with variations and passing the ball around the body (at the level of 0.00). In all 5 tests performed with the ball, result improvement in the final measurement was achieved. The highest and informationally very important result improvement was achieved in both tests which measured SMA Ball manipulation: Dribbling with variations (23%) and passing the ball around the body (10%).